2009
DOI: 10.3329/jsr.v2i1.2724
|View full text |Cite
|
Sign up to set email alerts
|

BER Performance Analysis of a Concatenated Low Density Parity Check Encoded OFDM System in AWGN and Fading Channels

Abstract: In this paper, we investigate the bit error rate (BER) performance of a concatenated low density parity check (LDPC) encoded orthogonal frequency-division multiplexing (OFDM) system on color image transmission. In FEC concatenated channel coding, the OFDM wireless communication system incorporates 1/2-rated convolution encoder under various digital modulations (QPSK, 8PSK, QAM, 8QAM, 16QAM and 32QAM) over an additative white gaussian noise (AWGN) and other fading (Raleigh and Rician) channels. Computer simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…Zahid Hassan et al [10] shown that the performance of the WiMAX system in digital image transmission over AWGN channel is comparatively better as compared to Rayleigh and Rician fading channels. The concatenated channel coding scheme with low-density parity-check and convolutional codes in OFDM based system is very much effective in proper identification and retrieval of transmitted digital image in noisy and fading environment [11]. Simulation of WiMAX Physical layer using Simulink and Matlab is described in [12].…”
Section: Related Workmentioning
confidence: 99%
“…Zahid Hassan et al [10] shown that the performance of the WiMAX system in digital image transmission over AWGN channel is comparatively better as compared to Rayleigh and Rician fading channels. The concatenated channel coding scheme with low-density parity-check and convolutional codes in OFDM based system is very much effective in proper identification and retrieval of transmitted digital image in noisy and fading environment [11]. Simulation of WiMAX Physical layer using Simulink and Matlab is described in [12].…”
Section: Related Workmentioning
confidence: 99%
“…This system uses the Set Partitioning in Hierarchical Trees (SPIHT) as a type of a source coding technique. In addition to advantages of LDPC code, there is another technique that come to the forefront of technology, namely orthogonal frequency division multiplex (OFDM) [8]. In [9], a combination between QC-LDPC and MIMO OFDM scheme is proposed to reduce the Peak Average Power Ratio (PAPR) which is considered one of the challenges in the OFDM systems.…”
Section: Introductionmentioning
confidence: 99%
“…The BER performance of a concatenated LDPC encoded OFDM system is studied by M.D. Haque et al [19] and concluded that the proposed system is very much effective in proper identification and retrieval of transmitted color image in noisy and fading environment. M. M. Hossain et al [20] also studied the impact of LDPC on the performance of an OFDM system under various digital modulations over an AWGN and other fading channels and they shown that the proposed system with deployment of QAM modulation is highly effective to combat inherent interferences and to retrieve the transmitted black and white image properly under noisy and fading situations.…”
Section: Introductionmentioning
confidence: 99%